STRATEGI PEMASARAN DAN PENGOLAHAN GULA AREN DI DESA BULUH AWAR SUMATERA UTARA - Juliana br. Simbolon; Roida Ervina Sinaga; Jupianus Sitepu; Dedi Erno Sinaga (JURNAL AGROTEKNOSAINS, 2022)
The study “Marketing and Processing Strategies of sugar palm in Buluh Awar village, North Sumatera. The aim of this study is to discover how the internal and external factors that af ect palm sugar processing and how the marketing and processing of sugar palm in Buluh Awar village, North Sumatera. This study carried out from October 2021 to March 2022. This study used sample collecting by sensus, in this study the sample used is 20 respondens. The sample in this study was the owner of the sugar palm factory who was in the Buluh Awar village, North Sumatera. Currently the challenge faced by agro-sugar palm industries is marketing of limited products at only traditional market in Deli Serdang regency and Medan city. Adjacent to it, the product creation runs through the order, the manufacturer acts as the recipient of the price